Byzantine military organization on the Danube, 10th-12th centuries - Madgearu, Alexandrum (East Central and Eastern Europe in the Middle Ages, 450-1450, 2013)
"The current state of research on this contact area between Byzantium and East Central Europe during a troubled period invites a new synthesis of the most recent finds and interpretations. No such comprehensive work addressing both literary and archaeological evidence exists for the history of the Byzantine Danubian provinces in the 10th-12th c. The main purpose Alexandru Madgearu's book is to establish a chronology for the provincial organization and for the development of the Danubian frontier. First a shield against the Rus', the province of Dristra, later called Paradunavon, became further a contact and conflict area with the Pechenegs and Cumans, turned by the end of the 11th century in a half-open space, according to the new strategy of Alexius I Comnenus"--Back cover.